WhatsApp e a prática do jornalismo regional nas redações jornalísticas da TV Anhanguera e CBN Tocantins - Mendonça, Fernanda Alves de (2024)
This dissertation investigates the relationship between the WhatsApp application and journalism, with the guiding question being: how has WhatsApp been used in the regional coverage developed by news outlets in Palmas? To answer this question, TV Anhanguera Tocantins, a TV station affiliated with Rede Globo, and CBN Tocantins, a radio station focused solely on journalism, were selected as the objects of analysis. The general objective is to investigate how these two broadcasters use the application to develop regional journalism in their production routine. The specific objectives are: a) to map the signal range and news coverage of the stations investigated; b) to observe how WhatsApp is inserted into the environment of the two newsrooms studied; and c) to learn about the characteristics of regional practice from the journalists' perceptions. The theoretical framework includes considerations about the relationship between technology and journalism, the Newsmaking hypothesis, and the characteristics of regional and local journalism. To achieve the proposed objectives, three methodological stages were adopted: 1) an exploratory survey of Palmas news outlets and information on institutional WhatsApp; 2) systematic observation in the newsrooms of TV Anhanguera and CBN Tocantins; and 3) semi-structured interviews with journalists working in the two newsrooms selected for the study. An important and unprecedented finding in the local context was the mapping of the institutional WhatsApp of news outlets in Palmas. It identified 26 outlets that use a number exclusively for news production. In addition to this, it was possible to discover information known only orally by the professionals and without academic records. This is the case with the news coverage map of the broadcasters investigated. From the point of view of regional production, it was found that WhatsApp contributes significantly to reducing the need to travel to cover stories outside the media outlets' headquarters, while at the same time strengthening access and contact with remote communities in the interior of the states. It was also found that the app is present at all stages of news production for both outlets. There is a clear dependence of newsrooms on WhatsApp, as it facilitates the production processes in the news architecture, brings sources closer together and makes the work of investigating faster. On the other hand, the app overloads journalists, who find themselves immersed in a sea of information and misinformation, as well as showing that the workday doesn't end when they leave the newsroom, but is extended by the connectivity provided by the internet and digital media.